Session 1, Panel 1, Storytelling, Peace and Conflict Resolution, Full Panel. - Jarvis, Dale (2010)
Storytelling, Peace and Conflict Resolution Panel at the 18th Annual Conference of Storytellers of Canada-Conteurs du Canada.